Woolly hair with palmoplantar keratoderma without cardiac abnormality: A rare case report - Saritha Mohanan; Alagammai Krishnappan; Udayashankar Carounanidhi; Ramachandran V Bhat (Wolters Kluwer Medknow Publications, 2020)
Woolly hair is a rare hair shaft abnormality characterized by extremely curly hair. It can occur in isolation or be associated with palmoplantar keratoderma (PPK) and cardiac defects. Here, we report a 3-year-old child with woolly hair and PPK without any cardiac manifestations. We report this case because of its rarity and to stress the importance of cardiac assessment in children with woolly hair.